The effects of special fabric-based exercises on physical fitness among the elderly in Na O Subdistrict Administrative Organization, Muang District, Loei Province - Seaburin, Worasit; Sripoka, Jaratsri; Panyakham, Artith; Kanpetta, Yupaporn; Bumrung, Neranoch; Hiruntrakul, Ashira (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to examine the effects of a fabric-based exercise program on the physical fitness of the elderly individuals in the Na O Subdistrict Administrative Organization area. A total of 45 participants, aged 60-79 years, were assessed for physical fitness indicators, including body weight, body mass index (BMI), muscle strength, flexibility, and endurance of the cardiovascular and circulatory systems. The participants were selected by using purposive sampling technique and engaged in a fabric-based exercise program 3 days per week for 12 weeks. The results showed that before joining the program and 12 weeks after participating in the program, there was no difference in average mean of body weight, BMI, endurance, flexibility, and the 2-minute standing knee up and down test (p > 0.05). However, the muscle strength statistically significant increased (p < 0.05). An exercise program using fabric is a beneficial activity for increasing muscle strength in older adults, as the fabric is harmless in terms of weight on the joints, and it can be positioned in easy movements. Additionally, fabric is commonly available in daily life and can be used to promote health when correct training postures are applied according to natural movement patterns.